FORMATION MULTIFUNCTIONAL COMPLEX IN THE ZONES OF INFLUENCE BY AUTOMOBILE COMMUNICATIONS - , Н. І., Є. В. (Municipal economy of cities. Series: «Economy science», 2013)
Based on the analysis of current practices and theoretical research papers revealed a number of contradictions between architectural and urban complexes that form a multi-functional structures in the zone of the main motor of communication. The basic problem is dominant, the purpose and design of the solution model - an example of a hypothesis Kharkiv.